Adaptive Interplay between Feeding Preference and Structure of the Upper Digestive Tract in African Green Bee-eater (Merops viridissimus cleopatra) - Basha, Walaa A.A.; Hassan, Said A.M.; Saad, Enas M.; Salah-Eldein, Ahmed M.; Elsayed, Ahmed K. (Journal of Advanced Veterinary Research, 2024)
Wild bird research, particularly investigations of the interplay between feeding habits, diet, and alimentary tract anatomy, offers a captivating avenue for scientific exploration. While numerous studies have delved into the upper digestive tracts of various avian species, there remains a dearth of data on the upper digestive tract anatomy of the African green bee-eater (AG bee-eater, Merops viridissimus cleopatra). This study aimed to bridge this knowledge gap by elucidating the gross, microscopic, and histochemical features of the esophagus and stomach in AG bee-eaters, shedding light on their food preferences, and feeding habits. Ten adult, apparently healthy AG bee-eaters were examined, revealing structural organizations of the esophagus, proventriculus, and gizzard that parallel those observed in other avian species. Key findings encompass a protective mucous layer in the esophagus and proventriculus, coupled with a moderately thick cuticle, guarding against harm from stinging insects like bees and wasps. The upper digestive tract houses numerous mucous-secreting glands, secreting both protective acidic mucin and enzymatic-neutral mucins. The proventriculus, featuring a thin wall and abundant glandular activity, equips AG bee-eaters with vital gastric enzymes for digesting their high-protein diet. This adaptation aligns with the bird’s compact upper digestive tract, well suited for processing relatively small food particles. Additionally, the ventriculus’s muscular layer, moderately thick, aligns with the moderately coarser texture of the bee-eater’s dietary preferences. Overall, this study unveils crucial anatomical adaptations enabling AG bee-eaters to thrive on a diet dominated by stinging insects.